Sifat Listrik Telur Ayam Kampung Selama Penyimpanan - J Juansah; Irmansyah Irmansyah; Kusnadi Kusnadi (Faculty of Animal Science, Bogor Agricultural University, 2009)
Study on eggs properties, based on electrical measurement (conductance and capacitance) was carried out using alternating current signal on frequency variation from 10 Hz to 100 kHz. The electrical properties correlated to physical properties of eggs i.e haugh unit, pH and viscosity. The albumen and yolk of native eggs, which were placed in the cell system from acrylic and electrode plate conductor of cuprum, were used as samples. Hi LCR Tester Hioki with dual probe (modified from four probes) was used to measure electrical properties of samples. This equipment was provided with fixed current source but varies in frequency. The conductance of yolk and albumen increased exponentially if frequency signal was boosted up. The electrical conductance range of albumen was higher than yolk on all frequencies. The capacitance property decreased if frequency signal was boosted up. The decrease was exponential especially at frequency under 100Hz. The albumen capacitance was lower than yolk. The viscosity of yolk and albumen during storage was decreasing. The value of pH was not affected. The pH of albumen was between 9 and 10, and yolk was about 6. Multiple regression method was used to get empiric equation of electrical conductance, capacitance, HU and viscosity. The best correlation between electrical parameter and physical properties is conductance equation of HU and viscosity at 1 kHz. Key words: electrical properties, conductance, capacitance, native chicken, egg